Corrosion behavior of oxide ion conductors for high‐temperature direct electrochemical metal oxide reduction. Issue 1 (6th October 2020) - Hwang, Kuk‐Jin; Shin, Miyoung; Lee, Myung‐Hyun; Lee, Heesoo; Shin, Tae Ho
Abstract: The corrosion behaviors of high oxide ion conductors using solid oxide membrane (SOM) electrolysis were investigated in practical operating conditions (current load or molten CaF2 ‐NaF‐CaO eutectic salt). In previous researches, yttria‐stabilized zirconia (YSZ), which is widely used in SOM electrolysis due to its good mechanical properties and ionic conductivity at high temperature, has several problems including phase transition due to yttrium ion dissolution, which results in decreased current efficiency and severe fracture of SOM tube. Thus, we introduced oxide ion conductors with a higher ionic conductivity than that of YSZ to exploit its excellent current efficiency and long‐term stability. In this study, we investigated the phase stability of Sr‐ and Mg‐doped lanthanum gallate (LSGM), Sc‐doped zirconia (ScSZ) and Gd‐doped ceria (GDC) using the structural analysis methods. Phase transition of LSGM and ScSZ easily occurred than that of GDC. GDC showed fairly tolerable stability; the molten salt ions were found only 10 μm deep on the surface, and the ions hardly penetrated the interior of bulk. However, LSGM ( 40 μm) and ScSZ ( 100 μm) showed a deep cation ion infiltration depth from the surface and severe surface corrosion was observed on the surface of LSGM and ScSZ.